2019
DOI: 10.1155/2019/8269695
|View full text |Cite
|
Sign up to set email alerts
|

Depression Episodes Detection in Unipolar and Bipolar Patients: A Methodology with Feature Extraction and Feature Selection with Genetic Algorithms Using Activity Motion Signal as Information Source

Abstract: Depression is a mental disorder which typically includes recurrent sadness and loss of interest in the enjoyment of the positive aspects of life, and in severe cases fatigue, causing inability to perform daily activities, leading to a progressive loss of quality of life. Monitoring depression (unipolar and bipolar patients) stats relays on traditional method reports from patients; however, bias is commonly present, given the patients’ interpretation of the experiences. Nevertheless, to overcome this problem, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…We identified 5 additional publications relevant to this review by backward and forward reference list checking. Overall, 54 publications were included in the current review 16 – 69 , and 38 of them were included in the meta-analyses 16 21 , 24 29 , 31 , 35 , 36 , 38 , 41 , 42 , 45 – 50 , 52 , 53 , 56 66 , 69 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…We identified 5 additional publications relevant to this review by backward and forward reference list checking. Overall, 54 publications were included in the current review 16 – 69 , and 38 of them were included in the meta-analyses 16 21 , 24 29 , 31 , 35 , 36 , 38 , 41 , 42 , 45 – 50 , 52 , 53 , 56 66 , 69 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…40 Regarding major depressive disorder (MDD) and schizophrenia detection, Galvan et al presented a feature selection and feature extraction with genetic algorithms methodology to detect depressive episodes in bipolar and unipolar patients. 41 The experimental results revealed that the proposed model with a feature extraction approach reached a value of 0.734 for the area under the curve (AUC). The authors concluded that it is possible to differentiate between depressive states by using the activity signal from a smart-band, providing a real-time preliminary and automated tool for physicians to support the diagnosis of depression.…”
Section: Literature Reviewmentioning
confidence: 96%
“…For example, GAs have been used on iris image reconstruction from binary templates [17]. Galvan et al [18] used GAs to perform feature selection for a depression detection model based on actigraphy signals.…”
Section: Genetic Algorithmsmentioning
confidence: 99%